Preliminaries

$$$$L_s(f * x) == f(s**(- 1) * x), forall s > 0

Preliminaries

$$$$(L_s(f) star psi) x == int(L_s(f * x__deriv) psi(x__deriv -

x) dx__deriv == int(f(s**(- 1) * x__deriv) psi(x__deriv - x)

dx__deriv))

== s * int(f(s**(- 1) * x__deriv) psi(s(s**(- 1) * x__deriv

- s**(- 1) * x)) d(s**(- 1) * x__deriv) == s L_s(f star L_s**(-

1)(psi)) x)

Preliminaries

$$$$L_s**(- 1)(psi_sigma * x) == psi_sigma(s * x) == s**(- 1) *

psi_(s**(- 1) sigma)(x)

Preliminaries

$$$$L_s(f * x) == f(s**(- 1) * x), forall s > 0

Preliminaries

$$$$(L_s(f) star psi) x == int(L_s(f * x__deriv) psi(x__deriv -

x) dx__deriv == int(f(s**(- 1) * x__deriv) psi(x__deriv - x)

dx__deriv))

== s * int(f(s**(- 1) * x__deriv) psi(s(s**(- 1) * x__deriv

- s**(- 1) * x)) d(s**(- 1) * x__deriv) == s L_s(f star L_s**(-

1)(psi)) x)

Preliminaries

$$$$L_s**(- 1)(psi_sigma * x) == psi_sigma(s * x) == s**(- 1) *

psi_(s**(- 1) sigma)(x)